The Budapest school : beyond Marxism - Dorahy, J. F. (Social and critical theory, 2019)
The Budapest School: Beyond Marxism represents the first systematic and comprehensive study of the post-Marxist writings of the Budapest School to be published in English. The School itself has long been known in English-speaking circles for its neo-Marxist critique of the now-defunct Soviet system. The Budapest School: Beyond Marxism enriches this understanding by situating the confrontation with 'actually existing socialism' as but one moment, however formative, within a much richer and much more theoretically relevant philosophical itinerary. From the early critique of alienation through to the contemporary critical theories of modernity, The Budapest School: Beyond Marxism charts the evolution of the School's thinking with a specific emphasis on the themes of culture, critique, history and the contingency of modern subjectivity.